A Systematic Review of the Literature on Early Vocalizations and Babbling Patterns in Young Children. (November 2018) - Morgan, Lydia; Wren, Yvonne E.
Children's speech development begins in infancy. The pattern of this development has been explored in studies over a number of years using a range of research methodology and approaches to investigation. A systematic review of the existing literature was carried out to determine the collective contribution of this literature to our understanding of early vocalizations and babbling through the period 9 to 18 months. Eight bibliographic databases were searched as well as the Cochrane library. Thirteen studies were identified for inclusion, which were mostly longitudinal observational case series. The review identified progressive increases in the complexity and volume of infants' early vocalizations through the period. It also found a broad order of phonological acquisition. Although the studies in this review demonstrated marked individual variation, the review provides indicative patterns of development which can be used as a basis to explore relationships with later speech development in future studies.